The rheological properties of multifunctional shear thickening materials and their application in vehicle shock absorbers. (7th July 2021) - Liu, Bing; Du, Chengbin; Wang, Lingyun; Fu, Yankai; Song, Ling
Abstract: A composite with both shear thickening (ST) and magnetorheological (MR) properties is fabricated by composing carbonyl iron powder into an ST matrix. The rheological properties are studied and the relative ST effect of the samples prepared under vacuum and non-vacuum conditions are compared. Then, the hydraulic oil in a vehicle hydraulic shock absorber is replaced with ST gel and ST fluid. The compression and rebound forces of the shock absorber containing hydraulic oil and ST fluid are tested and compared. Equal amounts of multifunctional ST fluid (MSTF, self-made) and MR fluid (self-made) are poured into an MR shock absorber and the performances are compared against the commercial MR shock absorber. Finally, the comprehensive performance and forces are improved by replacing SiO2 with the silica powder due to the smaller mean particle size.